Probes for 4th Generation Constituents of Dark Atoms in Higgs Boson Studies at the LHC - M. Yu. Khlopov; R. M. Shibaev (Advances in High Energy Physics)
The nonbaryonic dark matter of the Universe can consist of new stable charged species, bound in heavy neutral “atoms” by ordinary Coulomb interaction. Stable U- (anti-U)quarks of 4th generation, bound in stable colorless (U- U- U-) clusters, are captured by the primordial helium, produced in Big Bang Nucleosynthesis, thus forming neutral “atoms” of O-helium (OHe), a specific nuclear interacting dark matter that can provide solution for the puzzles of direct dark matter searches. However, the existence of the 4th generation quarks and leptons should influence the production and decay rates of Higgs boson and is ruled out by the experimental results of the Higgs boson searches at the LHC, if the Higgs boson coupling to 4th generation fermions is not suppressed. Here, we argue that the difference between the three known quark-lepton families and the 4th family can naturally lead to suppression of this coupling, relating the accelerator test for such a composite dark matter scenario to the detailed study of the production and modes of decay of the 125.5 GeV boson, discovered at the LHC.